Biodegradable Organic Transistors: Biocompatible and Biodegradable Organic Transistors Using a Solid‐State Electrolyte Incorporated with Choline‐Based Ionic Liquid and Polysaccharide (Adv. Funct. Mater. 29/2020). (16th July 2020) - Jo, Young Jin; Kim, Heyn; Ok, Jehyung; Shin, Yiel‐Jae; Shin, Joo Hwan; Kim, Tae Hee; Jung, Youngmee; Kim, Tae‐il
Abstract : In article number 1909707, Tae‐il Kim and co‐workers demonstrate a biodegradable and biocompatible solid‐state electrolyte for organic transistors based on a choline‐based ionic liquid and polysaccharide, which serves as the substrate and dielectric with good reliability under mechanical deformation and low‐voltage operation. This approach can introduce the main component of soft bio‐integrated electronics by measuring signals from the skin and other human organs.